Ottawa materials, C. F. Voegelin Papers - Voegelin, C. F. (Charles Frederick), 1906-1986; Williams, Angeline (1925)
Two items relating to the Odawa (Ottawa) language have been identified in the C. F. Voegelin Papers. They are both in Subcollection I. They consist of an "Ottawa" file with several pages of handwritten linguistic notes in Series V. Research Notes, Subseries V-A: Language Notes; and a file labeled "Williams, Angeline--Genealogy" with genealogical information about the Williams family in Series V. Research Notes, Subseries V-C: Other. Angeline Williams was an Odawa language consultant who worked with C. F. Voegelin, Erminine Wheeler-Voegelin, and Leonard Bloomfield, and participated in a field methods course taught by Voegelin and Bloomfield.